Effect of Liquid Organic Fertilizer (POC) Pineapple Peel and Trichoderma Sp. on the Growth and Yield of Cayenne Pepper (Capsicum Frutescens) Variety Ori 212: Pengaruh Pupuk Organik Cair (POC) Kulit Nanas Dan Trichoderma Sp. Terhadap Pertumbuhan dan Hasil Cabe Rawit (Capsicum Frutescens) Varietas Ori 212 - Farabi, Ahmad Al; Prihatiningrum, Andriani Eko (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the interaction of the effect of giving liquid organic fertilizer (POC) pineapple peel and giving Tricoderma sp. on the vegetative growth of cayenne pepper (Capsicum frutescens) ORI 212 variety. This study uses a quantitative method with a Randomized Group Design (RAK) arranged factorially, consisting of 2 factors, namely the dose of organic fertilizer (POC) Pineapple peel and Thricoderma sp, repeated 3 times. The observation variables that will be calculated in this observation include Plant Height (cm), Stem Diameter, Fruit Weight, Number of Branches, Number of leaves, Flowering Age (days), Number of Flowers (flowers) and Number of Fruits (fruits). Data were analyzed using analysis of variance (anova), if there was an effect, it was continued with the honest real difference test (BNJ). The results showed that there was an interaction effect of giving liquid organic fertilizer (POC) pineapple peel and Thricoderma sp, on vegetative growth, namely plant height, fruit weight, number of branches, number of leaves, flowering age, number of flowers and number of fruits of cayenne pepper (Capsicum frutescens) ORI 212 variety, but there was no effect on the observation of stem diameter.